Gambaran Perceived Long-Term Effect dari Bullying pada Individu Dewasa yang Pernah Menjadi Korban - Hoshael Waluyo Erlan (Jurnal Ilmiah Psikologi MIND SET, 2011)
This study aims to discover the long-term effects of bullying on adult individuals who have been affected by bullying. The subjects of this study are three people, comprising two men and one woman, who were affected by bullying when they were insenior high school. All subjects testify that they were undergoing bullying about two times or more in a week, for at lease two years. Two subjects were bullied at private school and one at goverment-run school. This study uses qualitative method with in-depth interview techniques. It reveals that the subjects perceive long-term effects such as shame, anxiety, and difficulty in establishing social relationships during their adulthood. The study discovers that bullying has a serious impact, and it will remain if not handled properly.